The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1073/pnas.92.18.8333
|View full text |Cite
|
Sign up to set email alerts
|

Disparate actions of hydroxyurea in potentiation of purine and pyrimidine 2',3'-dideoxynucleoside activities against replication of human immunodeficiency virus.

Abstract: We and other groups have recently reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…At the conceptual level, understanding how an inhibitor that should have identical effects on all four activities of rNDP reductase achieves apparent selective inhibition of just one of those activities in vivo relates to our long-standing interest in using in vitro enzymology to learn how enzymes behave within their natural environment, the living cell. At the practical level, hydroxyurea has been used for some time as an anticancer agent, which targets ribonucleotide reductase, and HU has shown activity as an antiviral agent in HIV-infected cells (6,19,20). In these more recent studies, HU displayed a synergistic effect when applied together with 2Ј,3Ј-dideoxyinosine, but only additive effects in combination with dideoxycytidine or dideoxyuridine.…”
Section: Discussionmentioning
confidence: 99%
“…At the conceptual level, understanding how an inhibitor that should have identical effects on all four activities of rNDP reductase achieves apparent selective inhibition of just one of those activities in vivo relates to our long-standing interest in using in vitro enzymology to learn how enzymes behave within their natural environment, the living cell. At the practical level, hydroxyurea has been used for some time as an anticancer agent, which targets ribonucleotide reductase, and HU has shown activity as an antiviral agent in HIV-infected cells (6,19,20). In these more recent studies, HU displayed a synergistic effect when applied together with 2Ј,3Ј-dideoxyinosine, but only additive effects in combination with dideoxycytidine or dideoxyuridine.…”
Section: Discussionmentioning
confidence: 99%
“…2a). HU has been shown to preferentially deplete dATP pools in mammalian cells (25,26), and there was a tendency for purine (particularly dATP) pools to fluctuate acutely whenever threonine metabolism and RNR activity were perturbed in combination (Fig. 4 a and b).…”
Section: Functional Interactions Between Dntp and Threonine Metabolismmentioning
confidence: 99%
“…The effect of HU on HIV replication might be mediated by two molecular mechanisms: (i) depletion of intracellular levels of dATP, resulting in a favorable shift of the purine analogue (ddI) triphosphate/dATP ratio; or (ii) enhancement of the mammalian pyrimidine kinase activities in salvage pathways, resulting in increased phosphorylation of the anti-HIV pyrimidine analogues (zidorudine [AZT], 3TC, and ddC). Several in vitro and in vivo studies have demonstrated the benefit of adding HU to anti-HIV therapeutic regimens that contain ddI, adefovir, d4T, AZT, 3TC and/or ddC (5,6,12,18,20). HU might also inhibit HIV replication by decreasing T-cell proliferation.…”
mentioning
confidence: 99%